166 Efficacy of Dupilumab in Children With Uncontrolled, Moderate-to-Severe Type 2 Asthma, With and Without Evidence of Allergy Enrolled in Phase 3 VOYAGE. (11th October 2021) - Szefler, Stanley J; Bacharier, Leonard B; Maspero, Jorge F; Papadopoulos, Nikos; Domingo, Christian; Daizadeh, Nadia; Lederer, David J; Hardin, Megan; Jacob-Nara, Juby A; Deniz, Yamo; Gall, Rebecca; Ortiz, Benjamin; et al.
Abstract : The allergic phenotype is an important subset of asthma patients with type 2 inflammation. Dupilumab, a fully human monoclonal antibody, blocks the shared receptor component for IL-4/IL-13, key and central drivers of type 2 inflammation in multiple diseases. In phase 3 VOYAGE, add-on dupilumab 100mg/200mg (body weight ≤30kg/>30kg, respectively) every 2 weeks vs placebo, reduced severe asthma exacerbations by 59.3% (P<0.0001) and improved lung function in children aged 6 to <12 years with uncontrolled moderate-to-severe type 2 asthma (baseline blood eosinophils ≥150cells/µl or FeNO ≥20ppb). This analysis evaluated the efficacy of dupilumab in pediatric patients with type 2 asthma with/without evidence of allergic asthma (total serum IgE ≥30IU/mL and ≥1 perennial aeroallergen-specific IgE ≥0.35kU/L at baseline). Annualized severe exacerbation rate during the 52-week treatment period was assessed using a negative binomial model. 350 pediatric patients with type 2 asthma were enrolled: of which, 261 had evidence of allergic asthma and 89 did not. Baseline characteristics were similar between subgroups, except for prevalence of ongoing atopic comorbidities (99.6% vs 77.5%) and median levels of type 2 biomarkers (blood eosinophils: 540.00cells/µL vs 310.00cells/µL; FeNO: 28ppb vs 13ppb; total serum IgE: 657.00IU/mL vs 107.00IU/mL) which were all higher in patients with vs without evidence of allergic asthma. Dupilumab vs placebo significantly reduced annualized severe exacerbation rate by 62% (P<0.0001) in patients with, and 51% (P<0.05) in patients without evidence of allergic asthma. No significant interaction was observed between the treatment effect and evidence of allergic asthma. In the overall safety population, the incidence of treatment-emergent adverse events (TEAEs) was similar across treatment groups; the most common TEAE occurring more frequently in the dupilumab group was injection site erythema (12.9% dupilumab vs 9.7% placebo). The majority of pediatric type 2 asthma patients enrolled in VOYAGE had evidence of allergic asthma; these patients had very high levels of type 2 biomarkers. Dupilumab demonstrated efficacy in reducing severe asthma exacerbations in children aged 6 to <12 years with uncontrolled, moderate-to-severe type 2 asthma, with or without evidence of allergic asthma.